Peran Produser Dalam Program Sport Today di Sportstars MNC Channel - Tiara Yuniar Rizki; Donny Kurniawan (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
This research focuses on the role of the producer in the "Sport Today" program broadcast by Sportstars MNC Channels. This program requires careful coordination and attention to detail at every stage of production. The aim of this research is to understand how producers participate in the pre-production, production and post-production stages to produce quality programs. This research uses Gerald Millerson's theory which focuses on the television production process as a basis for explaining how the pre-production, production and post-production stages are managed by producers. This theory emphasizes the importance of careful planning at the pre-production stage, effective implementation at the production stage, and careful editing and final finishing at the post-production stage. The research method used is a qualitative approach with case studies as the main focus. Data was obtained through in-depth interviews, observation and analysis of documents related to the "Sport Today" production program. The research results show that the role of the producer is very important in ensuring success at every stage of production. The suggestion from this research is that producers continue to improve their abilities in planning, managing, administering and completing production as well as following relevant technological developments.